2014
DOI: 10.1101/gr.169532.113
|View full text |Cite
|
Sign up to set email alerts
|

Extreme expansion of the olfactory receptor gene repertoire in African elephants and evolutionary dynamics of orthologous gene groups in 13 placental mammals

Abstract: Olfactory receptors (ORs) detect odors in the environment, and OR genes constitute the largest multigene family in mammals. Numbers of OR genes vary greatly among species—reflecting the respective species' lifestyles—and this variation is caused by frequent gene gains and losses during evolution. However, whether the extent of gene gains/losses varies among individual gene lineages and what might generate such variation is unknown. To answer these questions, we used a newly developed phylogeny-based method to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
301
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 323 publications
(343 citation statements)
references
References 58 publications
28
301
1
1
Order By: Relevance
“…Through their use, we have demonstrated that olfaction and chemical crypsis can be investigated in a scientific setting. Although headspace analyses can provide important insight into chemical crypsis by revealing the volatiles associated with species, and is considered the next step within this ongoing investigation, in isolation these data do not necessarily consider ecological influences given that odour perception is receptor-driven [60], and varied across species [61]. Furthermore, we contend that chemical crypsis is likely to be a far more important autecological trait of many species, especially for predator and prey species that spend extended periods immobile.…”
Section: Discussionmentioning
confidence: 99%
“…Through their use, we have demonstrated that olfaction and chemical crypsis can be investigated in a scientific setting. Although headspace analyses can provide important insight into chemical crypsis by revealing the volatiles associated with species, and is considered the next step within this ongoing investigation, in isolation these data do not necessarily consider ecological influences given that odour perception is receptor-driven [60], and varied across species [61]. Furthermore, we contend that chemical crypsis is likely to be a far more important autecological trait of many species, especially for predator and prey species that spend extended periods immobile.…”
Section: Discussionmentioning
confidence: 99%
“…Both dogs and rodents (mice and rats) possess fewer olfactory receptor (OR) genes (∼811 and ∼1200, respectively; Keller and Vosshall, 2008;Niimura et al, 2014) compared to African elephants (∼2000), which possess the most of any mammal tested thus far (Niimura et al, 2014). This high number of OR genes suggests that the species may have a superior olfactory ability to discriminate between structurally similar scents (Niimura et al, 2014), thereby potentially increasing their olfactory resolution.…”
Section: Introductionmentioning
confidence: 96%
“…This high number of OR genes suggests that the species may have a superior olfactory ability to discriminate between structurally similar scents (Niimura et al, 2014), thereby potentially increasing their olfactory resolution. This, in conjunction with their problem solving abilities, memory retention and cognition function (Bates et al, 2007;Byrne et al, 2009;Chevalier-Skolnikoff and Liska, 1993;Hakeem et al, 2005;McComb et al, 2014;Moss, 1988), may contribute significant advantages in wayward scenarios such as traversing landmine-affected areas.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the OR repertoire from the African elephant genome listed 5000 ORs, of which, 40% are functional. 8 One of the primary challenges in the study of ORs is elucidating the mechanism(s) by which a few hundred ORs in mammals discriminate several thousand odorants from the environment, which singly or in combination produce distinct and identifiable odors. OR-odorant interactions are promiscuous: one OR is known to bind multiple odorants; odorants, in turn, are known to interact with more than one OR.…”
Section: Opinionmentioning
confidence: 99%